Psychological Impact of COVID-19 Epidemic on Adolescents: A Large Sample Study in China - Zhou, Jiawei; Wang, Yini; Bu, Tianyi; Zhang, Sijia; Chu, Haiyun; Li, Jiarui; He, Jingyun; Zhang, Yansheng; Liu, Xuan; Qiao, Zhengxue; Yang, Xiuxian; Yang, Yanjie (Frontiers in Psychiatry, 2021)
Background: The COVID-19 epidemic is a current major public health emergency. However, little is known about the psychological impact on adolescents during this pandemic. We aimed to assess the prevalence and influencing factors of depression, anxiety and posttraumatic growth (PTG) among adolescents in a large sample study. Methods: The cross-sectional study collected demographic data and mental health measurements from 175,416 adolescents covered all provinces and autonomous regions in mainland of China from February 23 to March 8, 2020. The status of depression, anxiety and PTG were assessed by patient health questionnaire 9-item, generalized anxiety disorder questionnaire 7-item and post-traumatic growth inventory. Results: The prevalence of depression, anxiety and PTG in adolescents was 35.9%, 28.0% and 45.6%, respectively. The prevalence of depression and anxiety in slight or severe epidemic areas were similar. Regression analysis showed that female and older age were associated with higher levels of depression, anxiety and lower levels of PTG. Having symptoms related to COVID-19, excessive attention to epidemic information, living in urban or severe epidemic areas and conflicting with parents during home quarantine were risk factors of depression, anxiety and PTG. The frequently communication with peers, exercise and receiving public welfare psychological assistance were protective factors. Poor family economic situation was significantly risk factor of depression and PTG. Conclusion: Our findings suggested that positive and negative psychological reactions coexist on adolescents in the face of pandemic. The factors associated with psychological problems and PTG which provided strategic guidance for maintaining adolescent’s mental health in China as well as worldwide during any public pandemics such as COVID-19.